1971
DOI: 10.1111/j.1476-5381.1971.tb07152.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on cardiac muscle of the β‐adrenoceptor blocking drugs INPEA and LB46 in relation to their local anaesthetic action on nerve

Abstract: Summary1. As a local anaesthetic on frog nerve, LB46 had 0 4 times the activity of procaine and 2 times that of INPEA. 2. In reducing the maximum rate of depolarization (MRD) of intracellularly recorded cardiac action potentials, LB46 was 20 times more potent than INPEA.3. As an antagonist of the chronotropic effect on atrial muscle and of the inotropic effects on ventricular muscle of isoprenaline the pA2 values for LB46 were 9 05 +015 and 9-30+0-06 respectively, and for INPEA 6-00+0x16 and 6-10+0'12.4. LB46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The interaction between verapamil and amrinone on the slow channels seems competitive since amrinone could not overcome the inhibitory effects of verapamil at the higher concentration (2 x 10-6M). The electrical effects of amrinone were not antagonized by pindolol, a 3-adrenoceptor blocking agent (Singh & Vaughan Williams, 1971;Shimizu, Iwamura, Kodama, Toyama & Yamada, 1978) suggesting that the P-adrenoceptors do not play a role in the action of amrinone on sinus node cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The interaction between verapamil and amrinone on the slow channels seems competitive since amrinone could not overcome the inhibitory effects of verapamil at the higher concentration (2 x 10-6M). The electrical effects of amrinone were not antagonized by pindolol, a 3-adrenoceptor blocking agent (Singh & Vaughan Williams, 1971;Shimizu, Iwamura, Kodama, Toyama & Yamada, 1978) suggesting that the P-adrenoceptors do not play a role in the action of amrinone on sinus node cells.…”
Section: Discussionmentioning
confidence: 95%
“…The electrical effects of amrinone were not antagonized by pindolol, a 3-adrenoceptor blocking agent (Singh & Vaughan Williams, 1971;Shimizu, Iwamura, Kodama, Toyama & Yamada, 1978) suggesting that the P-adrenoceptors do not play a role in the action of amrinone on sinus node cells. On the basis of the present results, it is concluded that amrinone has an intrinsic effect on sinus node pacemaker cells, increasing their spontaneous firing activity.…”
Section: Influence Ofpindololmentioning
confidence: 89%
“…Intracellular electrophysiologic studies of cardiac tissues yield detailed information on the pathologic processes underlying the origins of abnormal rhythms (53,59,74) and play an important role in uncovering the mechanism of action of existing and new antiarrhythmic drugs (23,70). In some instances, results from intracellular studies have also suggested new therapeutic uses for older drugs initially developed for other than antiarrhythmic therapy (4,(54)(55)(56). In general, however, these techniques have not been widely used in the design of new agents (47), most of which were and continue to be uncovered by testing in intact animal models (58).…”
mentioning
confidence: 99%
“…This is based on the observation that both types of drug inhibit the fast sodium current in cardiac cells and in nerve (Singh & Vaughan-Williams, 1971;Edwards et al, 1976;Hille, 1978;Gintant & Hoffman, 1984). It has been suggested that common molecular mechanisms may be involved for both types of drug and in both tissues (Hondeghem & Katzung, 1977).…”
Section: Introductionmentioning
confidence: 99%